Using automated patch clamp electrophysiology platforms in pain‐related ion channel research: insights from industry and academia - Bell, Damian C (Br J Pharmacol, 2017)
Automated patch clamp (APC) technology was first developed at the turn of the millennium. The increased throughput it afforded promised a new paradigm in ion channel recordings, offering the potential to overcome the time‐consuming, low‐throughput bottleneck, arising from manual patch clamp investigations. This has relevance to the fast‐paced development of novel therapies for chronic pain. This review highlights the advances in technology, using select examples that have facilitated APC usage in both industry and academia. It covers both first generation and the latest developments in second‐generation platforms. In addition, it also provides an overview of the pain research field and how APC platforms have furthered our understanding of ion channel research and the development of pharmacological tools and therapeutics. APC platforms have much to offer to the ion channel research community, and this review highlights areas of best practice for both academia and industry. The impact of APC platforms and the prospects of ion channel research and improved therapeutics for chronic pain will be evaluated. LINKED ARTICLES: This article is part of a themed section on Recent Advances in Targeting Ion Channels to Treat Chronic Pain. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.12/issuetoc